Association between programmed death-ligand 1 expression, immune microenvironments, and clinical outcomes in epidermal growth factor receptor mutant lung adenocarcinoma patients treated with tyrosine kinase inhibitors. (January 2020) - Yang, Ching-Yao; Liao, Wei-Yu; Ho, Chao-Chi; Chen, Kuan-Yu; Tsai, Tzu-Hsiu; Hsu, Chia-Lin; Su, Kang-Yi; Chang, Yih-Leong; Wu, Chen-Tu; Hsu, Chia-Chi; Liao, Bin-Chi; Hsu, Wei-Hsun; et al.
Abstract: Introduction: Besides being a predictive biomarker of response to immunotherapy in lung cancer in general, programmed death-ligand 1 (PD-L1) is not so well correlated with treatment outcomes of lung adenocarcinoma (ADC) harbouring epidermal growth factor receptor (EGFR) mutations, as reported studies are inconclusive and seldom addressed the issues of response to treatment and resistance. The primary objective is to evaluate the association of PD-L1 and EGFR tyrosine kinase inhibitor (TKI) efficacy, resistance, and relevant clinical outcomes. The secondary objective is to further explore the tumour microenvironments of EGFR mutant tumours with different PD-L1 expression. Methods and materials: Using immunohistochemical (IHC) staining, we retrospectively tested PD-L1 expression (Dako 22C3) in the pre-treatment tumours from advanced EGFR mutant lung ADC patients, of whom all were treated with TKIs. Multiplex IHC assay was applied for exploring immune cells in tumour microenvironments. Results: A total of 153 Taiwanese patients were enrolled in our study, of whom a majority of cases were female (58.9%) and non-smokers (75.8%). The objective response rate (ORR) to EGFR TKI and progression-free survival (PFS) were better in patients with PD-L1 expression <50% (ORR/PFS in PD-L1 0% versus 1–49% versus ≥50%: 65.6%/12.5 months versus 56.4%/12.8 months versus 38.9%/5.9 months,   P <  0.05). The multivariate analysis showed that PD-L1 <50% was an independent prognostic factor for longer PFS (hazard ratio (HR) 0.433, 95% confidence interval (CI) 0.250–0.751, P  = 0.003). Furthermore, tumours with higher PD-L1 expression were less likely to develop a secondary T790M mutation (T790M+ in PD-L1 0% versus 1–49% versus ≥50%: 53.7% versus 35.7% versus 10%, P  = 0.024). Multiplex IHC tests were applied in 15 cases and revealed a potential correlation between PD-L1, immune cells, and EGFR TKI responses. Conclusions: Lower pre-treatment PD-L1 is associated with better ORR, PFS, and higher frequency of T790M resistance in EGFR TKI-treated lung ADC patients. Highlights: Pre-treatment PD-L1 can predict TKI response in EGFR mutant lung adenocarcinoma (ADC). Pre-treatment PD-L1 can predict acquired T790M in EGFR mutant lung ADC after TKI therapy. PD-L1 negatively correlated with B cells, macrophages, and regulatory T cells in EGFR mutant ADC. Abundant tumour-infiltrating B cell is associated with good TKI response in EGFR mutant ADC. Pre-treatment PD-L1 may help select the most appropriate regimen for EGFR mutant ADC.